Application of building information modelling (BIM) six dimension (6D) in green buildings: a case study of sunshine and daylight analysis - Lillian Gungat,; Shen, Ling; Goh, Siew Fang; Wei, Guomin; Li, Minghe; Asmawan Mohd Sarman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Although a considerable amount of research has been focused on how building information modeling (BIM) helps improve sustainable construction, BIM(6D) model validation and efficient data analysis methods are still lacking. This study aims to provide the more effective research method and analytical method. The Greenjiansville Sunshine analysis software Sun2020 and daylight analysis software Dali2020 were used for 6D modeling and simulation and real simulation of a building outside the daylight range and time. The daylight coefficients, outdoor visual field observation rate, and daylight quality were calculated for the rooms inside the building. The results show that single the daylight statistics and analysis color map can not accurately analyze whether the actual daylighting meets the demand, but combined with Power BI comprehensive analysis can get fast and accurate results. This paper provides important guidance for building researchers and practitioners to better align BIM development with green building development in the future.